A Short-Term Intervention of High-Intensity Exercise and Anodal-tDCS on Motor Learning in Middle-Aged Adults: An RCT - Quinlan, Clare; Rattray, Ben; Pryor, Disa; Northey, Joseph M.; Coxon, James; Cherbuin, Nicolas; Andrews, Sophie C. (Frontiers in Human Neuroscience, 2021)
High-intensity exercise has enhanced motor learning in healthy young adults. Anodal-transcranial direct current stimulation (a-tDCS) may optimize these effects. This study aimed to determine the effects of acute high-intensity interval exercise either with or without a-tDCS on the learning and retention of a novel motor task in middle-aged adults. Forty-two healthy middle-aged adults (age = 44.6 ± 6.3, female = 76%) were randomized into three groups: exercise and active a-tDCS, exercise and sham a-tDCS, and a non-exercise and sham a-tDCS control. Participants completed a baseline testing session, followed by three intervention sessions 48-hours apart. The exercise groups completed 20-minutes of high-intensity exercise followed by a novel sequential visual isometric pinch task (SVIPT) while receiving 20-minutes of 1.5 mA a-tDCS, or sham tDCS. The control group completed 20-minutes of reading before receiving sham a-tDCS during the SVIPT. Learning was assessed by skill change within and between intervention sessions. Participants returned five to seven days after the final intervention session and performed the SVIPT task to assess retention. All three groups showed evidence of learning on the SVIPT task. Neither group displayed enhanced overall learning or retention when compared to the control group. High-intensity exercise with or without a-tDCS did not improve learning or retention of a novel motor task in middle-aged adults. The methodological framework provides direction for future research to investigate the potential of differing exercise intensity effects on learning and retention.